Acceleration of Production Process by Ergonomic Design - Belyamin; Iwan Susanto; M Sjahrul Annas; Hasan, Herry Patria (Jurnal Teknologika, 2024)
PT. XYZ experienced load imbalance with the production capacity of the D17D product line in the molded production area, The existence of gaps 70 seconds between the standard SOP time of 360 seconds and the actual process time of 430 seconds. This difference occurs due to each process being unbalanced, the results of the process are not the same. With the concept of conducting research in the field of direct production then analyzing the rubberistics of the production process, it is hoped that the problems that occur can be found solutions to eliminate young time (in vain). From the results of this study proves that designing Jig & fixture as a tool to reduce the imbalance of each process where in the Unloading pressing rubber process there is an ergonomic influence that causes the operator to experience MSDs so that production results do not reach the target. As a result, after designing a tool to help the unloading process of the D17D product rubber press machine in the molded area, there was an acceleration of the process where the SOP time was 360 seconds before repairs was carried out 430 seconds after repair to 340 seconds